1936
DOI: 10.1021/j150373a003
|View full text |Cite
|
Sign up to set email alerts
|

The Creeping of Saturated Salt Solutions.

Abstract: Two studies of creeping have been recorded. E. R. Washburn (4) tried various solutions and solid surfaces and noted the general nature of the phenomenon. He observed that creeping is found not only in aqueous solutions of electrolytes, but also in non-aqueous solutions (e.g, sulfur in carbon bisulfide), and occurs not only on glass, but also on porcelain and metals. J. G. F. Druce (1), in common with Washburn, found quantitative results practically impossible because of the large number of variables, but su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

1972
1972
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 2 publications
1
30
0
Order By: Relevance
“…The effect of the substrate hydrophobicity or hydrophilicity on the topological character of precipitates has been observed in other salts such as K 2 Cr 2 O 7 [34], ammonium chloride [13], potassium nitrate, potassium chloride, and ammonium chloride [13,38]. …”
Section: Effects Of Substrate Surface Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of the substrate hydrophobicity or hydrophilicity on the topological character of precipitates has been observed in other salts such as K 2 Cr 2 O 7 [34], ammonium chloride [13], potassium nitrate, potassium chloride, and ammonium chloride [13,38]. …”
Section: Effects Of Substrate Surface Characteristicsmentioning
confidence: 99%
“…The pioneering work on salt creeping along glass walls concluded that capillarity draws solution upward to the growth front through tiny spaces among crystallites or between the crystallites and the glass wall [37]. It is later suggested that the solution is transported over rather than under the crystallites, given the limited space between the growing crystals and the glass wall [13]. Yet, a recent study using a high-magnification microscope reveals that K 2 Cr 2 O 7 crystal growth is largely determined by the solution transport between the crystallites and the substrate [34].…”
Section: Introductionmentioning
confidence: 99%
“…. A more thorough scientific study was later performed by Hazlehurst et al (1936), who challenged Washburn's proposed mechanism: "It is difficult to picture how the capillaries are formed originally, for the protrusion of the crystals beyond the limits of the solution seems much like raising oneself by ones bootstraps . in much the same manner that it would have done if the bottom of the dish had been cracked."…”
Section: Droplets Of Ionic Solutions 309mentioning
confidence: 99%
“…If an initially dry solid is stood in a shallow tray of concentrated brine, salt will eventually begin to migrate up the side of the object, first as a translucent layer of fine crystals and later forming an outer skin of crystals in the form of dendritic outgrowths. This phenomenon was initially referred to as creep [7,8] but here it will be termed autogenous wicking. The process begins with evaporation causing the brine solution to become supersaturated, followed by the nucleation of crystals at the brine meniscus.…”
Section: (A) Salt Migration On Non-porous Surfacesmentioning
confidence: 99%